PERSEPSI GURU MATA PELAJARAN PENDIDIKAN PANCASILA DI SMP NEGERI 27 MUARO JAMBI TENTANG PELAKSANAAN PEMBELAJARAN DALAM KURIKULUM MERDEKA - Rahma Handayani; Hendra; Melisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teachers' perceptions of the implementation of the Independent Curriculum in Pancasila Education learning. The Independent Curriculum is part of an educational transformation effort oriented towards holistic student competency development through student-centered, flexible learning, and supporting character formation aligned with the Pancasila Student Profile. In the context of its implementation, teachers' perceptions play a strategic role because they influence the level of acceptance, readiness, and effectiveness of curriculum implementation in the school environment. This study used a qualitative approach with descriptive methods to gain an in-depth understanding of teachers' perspectives on the implementation of the Independent Curriculum. The research informants consisted of Pancasila Education teachers directly involved in the curriculum implementation process and with relevant teaching experience. Data collection was conducted through in-depth interviews, observation, and documentation. Subsequently, the data were analyzed through data reduction, data presentation, and conclusion drawing to produce a comprehensive interpretation of the phenomenon under study.